Changes in serum zinc and copper concentrations in patients with cardiovascular disease following cardiac surgery. Issue 19 (6th October 2022) - Moravvej, Zahra; Baradaran Rahimi, Vafa; Azari, Ali; Rahsepar, Amir Ali; Ghayour‐Mobarhan, Majid; Salehi, Maryam; Bigdelu, Leila
Abstract: The trace elements copper (Cu) and zinc (Zn) are essential for maintaining oxidative balance, and cardiac surgery is known to provoke an increase in oxidative stress. We investigated the variations in serum Zn and Cu concentrations before and after surgery in patients undergoing on‐ and off‐pump CABG and heart valve replacement. We performed a prospective study on patients undergoing on‐ or off‐pump CABG, or heart valve replacement surgery (48, 51, and 47 patients, respectively). Venous blood samples were obtained, and serum Cu and Zn concentrations were measured preoperatively, 24 h postoperatively, and the time of discharge. In addition, echocardiography was carried out on all patients before surgery and again on the day of discharge. We found the temporal changes in Cu, Zn, and Zn/Cu ratio were significantly different in all three groups of surgery ( p  < 0.05). In each group, Cu and Zn values and Zn/Cu ratio decreased at the 24‐h postoperative time and rose at the discharge time. There were no significant differences between surgery groups in the changes induced in Zn or Cu values ( p  > 0.05). In conclusion, the concentrations of Cu and Zn were markedly reduced after on‐ and off‐pump CABG and valve replacement surgery. This may suggest that supplementary Zn and Cu administration could be beneficial during open‐heart surgeries. However, more long‐term studies with more patients are needed to confirm this hypothesis. Abstract : In conclusion, the concentrations of Cu and Zn were markedly reduced after on‐ and off‐pump CABG and valve replacement surgery. Copper concentrations were inversely associated with cardiopulmonary bypass duration, implying the need to evaluate the precise role of CBP in inducing oxidative stress.